2005
DOI: 10.1038/sj.onc.1209050
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nuclear ribonucleoprotein A2 is a SET-binding protein and a PP2A inhibitor

Abstract: The oncoprotein SET participates in a diversity of cellular functions including cell proliferation. Its role on cell cycle progression is likely mediated by inhibiting cyclin B-cdk1 and the protein phosphatase 2A (PP2A). On identifying new SET cellular partners, we found that SET interacts in vitro and in vivo with the heterogeneous nuclear ribonucleoprotein A2 (hnRNPA2); a protein involved in various aspects of mRNA biogenesis. The SET-binding region of hnRNPA2 is the RNP1 sequence that belongs to the RNA-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 44 publications
1
27
0
2
Order By: Relevance
“…Significantly, all TSPY isoforms harbor the entire or part of a conserved domain of B160 amino acids, termed SET/NAP domain initially identified in the human SET oncoprotein and nucleosome assembly protein-1 (NAP-1) (Tsuchiya et al, 1995;Vogel et al, 1998). The SET/NAP proteins are structurally related and serve a wide range of biological functions, including cell-cycle regulation, histone chaperone, chromatin organization, transcription modulation and steroid receptor co-regulation (Adachi et al, 1994;Kellogg et al, 1995;Estanyol et al, 1999;Compagnone et al, 2000;Chai et al, 2001;Seo et al, 2001;Canela et al, 2003;Ozbun et al, 2003;Gamble et al, 2005;Kandilci and Grosveld, 2005;Vera et al, 2005;Kido and Lau, 2006). Currently, it is uncertain if these TSPY isoforms possess the same or different functions, retention of the SET/NAP domain suggests that this conserved domain could be important for their biological action(s).…”
Section: Introductionmentioning
confidence: 99%
“…Significantly, all TSPY isoforms harbor the entire or part of a conserved domain of B160 amino acids, termed SET/NAP domain initially identified in the human SET oncoprotein and nucleosome assembly protein-1 (NAP-1) (Tsuchiya et al, 1995;Vogel et al, 1998). The SET/NAP proteins are structurally related and serve a wide range of biological functions, including cell-cycle regulation, histone chaperone, chromatin organization, transcription modulation and steroid receptor co-regulation (Adachi et al, 1994;Kellogg et al, 1995;Estanyol et al, 1999;Compagnone et al, 2000;Chai et al, 2001;Seo et al, 2001;Canela et al, 2003;Ozbun et al, 2003;Gamble et al, 2005;Kandilci and Grosveld, 2005;Vera et al, 2005;Kido and Lau, 2006). Currently, it is uncertain if these TSPY isoforms possess the same or different functions, retention of the SET/NAP domain suggests that this conserved domain could be important for their biological action(s).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, although a role in proliferation of human cell lines was previously described, 61 and overexpression of HNRNPA2B1 has been found in PDAC cell lines 62 a direct role of HNRNPA2B1 in tumorogenesis was not proved until recently. Golan-Gerst and coworkers 47 showed, on the one hand, that NIH 3T3 overexpressing HNRNPA2B1 became transformed, formed colonies in soft agar and were tumorigenic in nude mice, and, on the other hand, that knock-down of HNRNPA2B1 in glioblastoma cells inhibited tumor formation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the PP2A subunit PR65/A, which is also overexpressed in BCR/ABL þ cells, may also contribute to PP2A inactivation, as PR65/A overexpression could sequester the catalytic or variable subunits or act as a PP2Ac inhibitor (Kamibayashi et al, 1992;Wera et al, 1995). Interestingly, it was recently reported that hnRNP A2, an hnRNP with high sequence, structure and function similarity with hnRNP A1, inhibits PP2A activity upon interaction with SET (Vera et al, 2006). Because also hnRNP A2 expression is induced by BCR/ABL (our unpublished observation), the hnRNP A2/SET-dependent inhibition of PP2A may represent another mechanism whereby BCR/ABL induces the loss of PP2A function in CML-BC.…”
Section: Bcr/abl and Pp2a: The Yin And Yang Of Blast Crisis CMLmentioning
confidence: 99%